Dynamic Control of Mitochondrial Ca2+ Levels as a Survival Strategy of Cancer Cells - Madreiter-Sokolowski, Corina T.; Gottschalk, Benjamin; Sokolowski, Armin A.; Malli, Roland; Graier, Wolfgang F. (Frontiers in Cell and Developmental Biology, 2021)
Cancer cells have increased energy requirements due to their enhanced proliferation activity. This energy demand is, among others, met by mitochondrial ATP production. Since the second messenger Ca2+ maintains the activity of Krebs cycle dehydrogenases that fuel mitochondrial respiration, proper mitochondrial Ca2+ uptake is crucial for a cancer cell survival. However, a mitochondrial Ca2+ overload induces mitochondrial dysfunction and, ultimately, apoptotic cell death. Because of the vital importance of balancing mitochondrial Ca2+ levels, a highly sophisticated machinery of multiple proteins manages mitochondrial Ca2+ homeostasis. Notably, mitochondria sequester Ca2+ preferentially at the interaction sites between mitochondria and the endoplasmic reticulum (ER), the largest internal Ca2+ store, thus, pointing to mitochondrial-associated membranes (MAMs) as crucial hubs between cancer prosperity and cell death. To investigate potential regulatory mechanisms of the mitochondrial Ca2+ uptake routes in cancer cells, we modulated mitochondria–ER tethering and the expression of UCP2 and analyzed mitochondrial Ca2+ homeostasis under the various conditions. Hence, the expression of contributors to mitochondrial Ca2+ regulation machinery was quantified by qRT-PCR. We further used data from The Cancer Genome Atlas (TCGA) to correlate these in vitro findings with expression patterns in human breast invasive cancer and human prostate adenocarcinoma. ER-mitochondrial linkage was found to support a mitochondrial Ca2+ uptake route dependent on uncoupling protein 2 (UCP2) in cancer cells. Notably, combined overexpression of Rab32, a protein kinase A-anchoring protein fostering the ER-mitochondrial tethering, and UCP2 caused a significant drop in cancer cells' viability. Artificially enhanced ER-mitochondrial tethering further initiated a sudden decline in the expression of UCP2, probably as an adaptive response to avoid mitochondrial Ca2+ overload. Besides, TCGA analysis revealed an inverse expression correlation between proteins stabilizing mitochondrial-ER linkage and UCP2 in tissues of human breast invasive cancer and prostate adenocarcinoma. Based on these results, we assume that cancer cells successfully manage mitochondrial Ca2+ uptake to stimulate Ca2+-dependent mitochondrial metabolism while avoiding Ca2+-triggered cell death by fine-tuning ER-mitochondrial tethering and the expression of UCP2 in an inversed manner. Disruption of this equilibrium yields cancer cell death and may serve as a treatment strategy to specifically kill cancer cells.